Self-Propelled Magnetic Dendrite-Shaped Microrobots for Photodynamic Prostate Cancer Therapy - Peng, Xia; Urso, Mario; Balvan, Jan; Masarik, Michal; Pumera, Martin (Angewandte Chemie (International ed. in English), 2022)
Photocatalytic micromotors that exhibit wireless and controllable motion by light have been extensively explored for cancer treatment by photodynamic therapy (PDT). However, overexpressed glutathione (GSH) in the tumor microenvironment can down-regulate the reactive oxygen species (ROS) level for cancer therapy. Herein, we present dendrite-shaped light-powered hematite microrobots as an effective GSH depletion agent for PDT of prostate cancer cells. These hematite microrobots can display negative phototactic motion under light irradiation and flexible actuation in a defined path controlled by an external magnetic field. Non-contact transportation of micro-sized cells can be achieved by manipulating the microrobot's motion. In addition, the biocompatible microrobots induce GSH depletion and greatly enhance PDT performance. The proposed dendrite-shaped hematite microrobots contribute to developing dual light/magnetic field-powered micromachines for the biomedical field.
Keywords: Prostatic Neoplasms; nádory prostaty; Micromotors; Humans; dendrity; fotochemoterapie; lidé; magnetické pole; Dendrites; Glutathione; Cargo Transportation; Tumor Cells; Male; Tumor Microenvironment; glutathion; nádorové mikroprostředí; Photochemotherapy; Micromachines; Magnetic Fields; mužské pohlaví; Photocatalysis